2018
DOI: 10.1088/2057-1976/aaa6aa
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of track structure and condensed history physics models for applications in radiation dosimetry on a micro and nano scale in Geant4

Abstract: Investigation of track structure and condensed history physics models for Investigation of track structure and condensed history physics models for applications in radiation dosimetry on a micro and nano scale in Geant4 applications in radiation dosimetry on a micro and nano scale in Geant4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 56 publications
8
55
0
Order By: Relevance
“…However, users must be cautious because, even under optimally-chosen simulation parameters, the differences between the CH and TS models of Geant4 may still be significant for low energy electrons (< 1 keV) and/or nanometer size targets (< 100 nm). The present findings are in agreement with recent studies on the performance of the low energy electromagnetic models of Geant4 [27,28] where it was concluded that simulations at the nanoscale strongly depend upon the target size, the physics model, and simulation Fig. 4.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…However, users must be cautious because, even under optimally-chosen simulation parameters, the differences between the CH and TS models of Geant4 may still be significant for low energy electrons (< 1 keV) and/or nanometer size targets (< 100 nm). The present findings are in agreement with recent studies on the performance of the low energy electromagnetic models of Geant4 [27,28] where it was concluded that simulations at the nanoscale strongly depend upon the target size, the physics model, and simulation Fig. 4.…”
Section: Resultssupporting
confidence: 93%
“…1a, 1b, and 1c we present the Δ (%) max for the CH models and for the different SL examined (tracking and production cuts = 10 eV). Penelope exhibits the largest differences from DNA option4 whereas Livermore has the best agreement with DNA option4, in agreement with recent findings [27,28]. Livermore DPK calculations also seem to be the least sensitive to SL variations.…”
Section: Dpk Profilessupporting
confidence: 89%
See 2 more Smart Citations
“…This functionality has provided a unique theoretical tool for investigating differences between sparse (or low linear energy transfer (LET)) and dense (or high-LET) ionization radiations at the nanometer level, which is not possible by other means [32]. MCTS codes have been the workhorse of theoretical microdosimetry, enabling systematic calculations of lineal energy spectra (the stochastic analog of LET), proximity functions, ionization cluster distributions, etc., which are used for explaining and predicting the quality factor or the relative biological effectiveness of different ionizing radiations [33][34][35][36][37][38][39]. In addition, quantitative estimates of the early "direct" DNA damage can be obtained by combining the spatial distribution of energy-transfer points (above a certain threshold) with the geometric structure of DNA [40][41][42][43][44][45].…”
Section: Particle Track Structure Codesmentioning
confidence: 99%